'Remoteness was a blessing, but also a potential downfall': traditional/subsistence and store-bought food access in remote Alaska during the COVID-19 pandemic - Ruby L Fried; Micah B Hahn; Patricia Cochran; Laura P Eichelberger (Cambridge University Press, 2023)
Abstract Objective: This study employs a strengths-based approach to assess food access in remote Alaska during the COVID-19 pandemic, identifying both the negative consequences of the pandemic on store-bought and subsistence/traditional food access and compensatory strategies used. Design: As a part of a larger study on the impacts of COVID-19 on daily life remote Alaskan communities, study data presented here were collected through key informant interviews (KII) and state-wide online surveys from 21 September 2020 to 31 March 2021 among remote Alaska community members. Setting: This study was conducted with residents of remote communities in Alaska, defined as those off the road system. Remote communities often have small or no grocery stores and rely on subsistence or traditional sources of food. Participants: KII participants (n 36) were majority female (78 %) and Alaska Native (57 %). Survey participants (n 615) were also majority female, 25-54 years old and most had had some post-secondary education or training. Results: Survey and interview data revealed that the pandemic had significant negative impacts on store-bought food access in remote Alaskan communities. Individuals also shared that locally available and wild harvested foods acted as a buffer to some of the loss of access to these store-bought foods, with some people sharing that the harvesting of wild and traditional foods served as a coping strategy during times of pandemic-related stress. Conclusions: The results from this study demonstrate that the remoteness of some Alaskan communities has been both a source of vulnerability and protection in terms of food access.